Multi-level design model and genetic algorithm for structural control system optimization. - Li, Q.S.
The integrated optimum problem of structures subjected to strong earthquakes and wind excitations, optimizing the number of actuators, the configuration of actuators and the control algorithms simultaneously, is studied. Two control algorithms, optimal control and acceleration feedback control, are used as the control of algorithms. A multi-level optimization model is proposed with respect to the solution procedure of the optimum problem. The characteristics of the model are analysed, and the formulation of each suboptimization problem at each level is presented. To solve the multi-level optimization problem, a multi-level genetic algorithm (MLGA) is proposed. The proposed model and MLGA are used to solve two multi-level optimization problems in which the optimization of the number of actuators, the positions of actuators and the control algorithm are considered in different levels. In problem 1, an example structure is excited by strong wind, and in problem 2, an example structure is subjected to strong earthquake excitation.
Keywords: Multi level design model; Genetic algorithm; Structural control